When Educational Videos Do Not Improve Learning: A Case Study on IPAS Achievement Among Fourth-Grade Students - Indri Alpionita; Mohammad Baihaqi (Journal of Elementary Education Research and Practice, 2025)
This study aims to analyze the effect of educational video media on students’ learning achievement in the IPAS subject at SDN 007 Balikpapan Barat. The research employed a quantitative pre-experimental design using a one-shot case study with 13 fourth-grade students as participants. Data were collected using a questionnaire consisting of 10 items and analyzed through validity testing, reliability testing, assumption testing, and hypothesis testing. The results of the t-test showed that the use of educational video media did not have a significant effect on students’ learning achievement (t = 1.550 < ttable = 2.201, p = 0.149). The coefficient of determination (R² = 0.179) indicated that educational video media contributed only 17.9% to the variance in student achievement. These findings suggest that educational videos, when used independently, are not sufficient to improve learning outcomes in IPAS. Greater instructional support and more varied teaching strategies may be required to optimize their effectiveness.